A Drosophila gene is subject to glucose repression - Benkel, Bernhard F. (1987)
Amylase-specific cDNA probes were used to assay amylase mRNA levels in third-instar larvae of Drosophila melanogaster. It is shown that there is a difference, of the order of 100-fold, in the mRNA levels between larvae that are fed 10% glucose and larvae of the same wild-type strain that are fed an equivalent diet lacking glucose. In fact, the glucose-fed larvae have barely detectable levels of amylase mRNA. This large difference in transcript abundance indicates that the glucose effect, which we previously characterized at the level of enzyme activity, probably reflects a change in the transcriptional activity of the amylase gene.